Formulation and physicochemical characterization of diethylaminoethyl dextran coated liposome as a drug carrier and its effect on the rheological properties of carbopol gel / Premanarayani Menon Narayanan Nair - Premanarayani Menon , Narayanan Nair (2017)
In search of improved topical delivery products, efforts are aimed to develop new drug carriers or modify existing drug carriers mainly to exhibit adequate penetration properties as well as to assure localization of the drug within the skin. Liposome has played a significant role in therapeutics as an effective drug carrier. However, physicochemical instability of liposomes reduces its possibilities and potentials to be used in drug delivery systems. The purpose of this work was to study the potential of diethylaminoethyl dextran (DEAE-DX) coated liposomes as drug carriers for topical applications. Thin film hydration method was employed to prepare three types of liposomes composed of lecithin, 1,2-dipalmitoyl-sn-glycero-3-phospocholine (DPPC) and 1,2-distearoyl-sn-glycero-3-phospocholine (DSPC), respectively. As stability is a general problem with liposomes, DEAE-DX was included in the liposome formulation to promote steric stabilization by coating the surface of the lecithin, DPPC and DSPC liposomes. It was found that liposomes stabilized by DEAE-DX were superior to the corresponding non-coated liposomes. The critical vesicular concentration (CVC) was determined in order to investigate the minimum concentration of lipid required to form vesicles via surface tension analysis. Also, the surface behavior of the lipids was investigated through surface tension analysis before and after the addition of DEAE-DX. All of the liposomes were evaluated based on their morphology, particle size and zeta potential. A thirty-five-day stability study showed that DEAE-DX coated liposomes were stable at room temperature. Encapsulation efficiencies of these liposomes were studied via the loading of curcumin as the hydrophobic drug and diphenhydramine hydrochloride (DPH) as the hydrophilic drug into the liposomes. An in vitro release experiment demonstrated a slower drug release profile for DEAE-DX coated liposomes compared to non-coated liposomes. Although liposomes are exhibited as potential carriers for the topical formulation, the practical application of these formulations onto the skin is less due to its liquid nature. In this study, liposome formulation was incorporated into carbopol gel in order to ease the mode of application. The rheological results indicated that presence of DEAE-DX coated liposomes in the gel has modified viscoelastic and flow characteristics of the gel. Furthermore, it was observed that the presence of DPH in the gel has lowered the storage modulus, G’ of the gel whereas curcumin has no significant effect on the rheological properties of carbopol gel.